전라남도 강진만에 도래하는 조류의 분포와 갯벌등급 - 신용운(Yong-Un Shin); 조해진(Hae-Jin Cho); 강태한(Tae-Han Kang); 김인규(In-Kyu Kim); 오홍식(Hong-Shik Oh); 이시완(Si-Wan Lee) (한국조류학회지, 2011)
본 연구는 2009년 8월부터 2010년 7월까지 전라남도 강진군 강진만에 도래하는 조류의 분포와갯벌 등급을 파악하기 위하여 이루어졌다. 조사결과, 관찰된 조류는 107종 11,060개체였으며, 우점종은 흰죽지, 청둥오리, 민물도요, 큰고니 등이었다. 조류들은 봄, 가을, 겨울에는 강진만 상류지역과 하류의 사내호를 중심으로 분포하였고, 여름철에는 전 지역에 고루 분포하는 것으로 나타났다. 갯벌등급은 보호지역인 순천만, 무안만과 같은 Ⅳ등급으로 판정되어 그 가치가 높은 것으로나타났다. 강진만은 하구둑이 없는 자연형습지이며, 출현하는 법적보호종도 13종으로 나타나 다른연안습지에 비해 많고, 특히 법적보호종인 큰고니의 주요 서식지로서 그 중요성은 크다고 할 수있다. This study was conducted a survey on birds visiting this area eleven times by season from August in 2009 to July in 2010 to look into the distribution of birds and grading assessment of the tidal flat at Gangjin Bay in Jeollanamdo. This survey results revealed that existed a total of 11,060 individuals of 107 species. The dominant species were Pochard (Aythya ferina), Mallard (Anas platyrhynchos), Dunlin (Calidris alpina) and Whooper Swan (Cygnus cygnus) in the order of dominancy. In summer, birds were observed over a wide area of Gangjin bay, and the other season, birds were mostly distributed in the upstream of Gangjin bay and Lake Sanae of outside region. Gangjin Bay grade level was same as the Muan Bay's grade and Suncheon Bay's grade. but Gangjin Bay is natural form wetlands that without estuary weir and wintering sites for Cygnus cygnus. In addition, for the total of 13 legally protected species including Whooper Swan (Cygnus cygnus), Gangjin bay has a special function of primary habitat in this area. KCI Citation Count: 5